Inculcating tolerance by multicultural based PPKn learning - G. Gunartati; Z. Zamroni; Abdul Gafur (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2017)
This study aims to: (1) describe the teaching conditions of multicultural-based PPKn implemented by SMA in DIY, (2) produce a feasible model of teaching PPKn based on multi-culture for inculcating tolerance for senior high school students , (3) find out the effectiveness of developed teaching model. This research was research and development adopting the procedural model of Borg Gall. The procedures were divided into four phases, namely: (1) the needs analysis phase (2) the development stage of models and expert judgment (3) testing and refining the model, and (4) dissemination phase. The experiment was conducted at SMA Jetis, SMA 2 Bantul, and SMA 2 Wates. The Subjects were teachers and students of XI class of those SMAs. The data analysis used the descriptive analysis and t-test to determine the effectiveness of the product. The results of the reaseach are as follow. First, the teaching of PPKn in SMA in DIY is still conventional and not yet exploring multicultural values. Second, teaching model of multicultural-based PPKn declared eligible by material experts, instructional experts and assessment of the teachers. And the third, the teaching model developed is effectively used in the teaching and learning. This is indicated by the significant differences in learning outcomes between the experimental and control groups. The effectiveness is proved by using t test that the result is significant (p 0.05), and the mean of experiment group is higher than the mean of the control group.